2010
DOI: 10.4047/jap.2010.2.4.148
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bone bed preparation with laser and conventional drill on the relationship between implant stability quotient (ISQ) values and implant insertion variables

Abstract: PURPOSEThe aim of this study was to investigate a comparison of implant bone bed preparation with Er,Cr:YSGG laser and conventional drills on the relationship between implant stability quotient (ISQ) values and implant insertion variables.MATERIALS AND METHODSForty implants were inserted into two different types of pig rib bone. One group was prepared with conventional drills and a total of 20 implants were inserted into type I and type II bone. The other group was prepared with a Er,Cr:YSGG laser and a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Histomorphologic aspects of the defects observed at day 0 demonstrated that, in contrast to the drills, which have a predetermined design, the laser osteotomy is created free hand with a 600‐μm‐diameter light bundle that impairs precise design of the osteotomy in deep regions, generating irregular defects. The difficulty in producing deep osteotomies with lasers was observed by other authors who used Er,Cr:YSGG lasers in the creation of surgical cavities for implants 15 , 23 , 24 . This limitation represents a technical challenge for a broader use of the equipment in bone surgeries in the non‐contact mode.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histomorphologic aspects of the defects observed at day 0 demonstrated that, in contrast to the drills, which have a predetermined design, the laser osteotomy is created free hand with a 600‐μm‐diameter light bundle that impairs precise design of the osteotomy in deep regions, generating irregular defects. The difficulty in producing deep osteotomies with lasers was observed by other authors who used Er,Cr:YSGG lasers in the creation of surgical cavities for implants 15 , 23 , 24 . This limitation represents a technical challenge for a broader use of the equipment in bone surgeries in the non‐contact mode.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty in producing deep osteotomies with lasers was observed by other authors who used Er,Cr:YSGG lasers in the creation of surgical cavities for implants. 15,23,24 This limitation represents a technical challenge for a broader use of the equipment in bone surgeries in the non-contact mode.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al. reported that the effects of bone bed preparation with an Er,Cr:YSGG laser on the relationship between implant stability quotient values and implant insertion variables were comparable with those of drilling in an in vitro study using pig rib bones. These studies demonstrated that the laser‐prepared fixture holes exhibited safe wound healing and that, clinically, the laser‐modified bone interface did not negatively affect the attachment between bone and the implant fixture.…”
Section: Implant Therapymentioning
confidence: 97%
“…19 Although there are many studies demonstrating the application of lasers in bone and soft tissue surgery during dental implantation, [1][2][3][4][5][17][18][19][20][21][22][23][24] only few evaluate their advantages in implant bed preparation. [25][26][27][28][29] The research by Seymen et al compared the differences between the planned and prepared implant beds for the erbium, chromium-doped yttrium scandium gallium garnet (Er,Cr:YSGG) laser group and the conventional drilling group in coronal and apical deviations. 25 The differences in the mean angular, coronal and apical deviations were reported to be marginally in favor of traditional drilling methods.…”
Section: Discussionmentioning
confidence: 99%